Analyzing the importance of financial resources for educational effectiveness: The case of Brazil. Issue 1 (2014) - ,; ,
Abstract : Purpose – Much has been done in the public organization performance management field and there are some established theories that account for what would improve performance, but there is little strong empirical evidence about the determinants factors to performance in developing countries. This paper aims to contribute to the knowledge in this area by providing some empirical evidence about the importance of management and resource for the local government performance.Design/methodology/approach – The paper presents a cross‐sectional investigation carried out with a sample of Brazilian municipalities. Data come from reliable sources, namely official databases. In order to ensure causality, regression and correlation analysis was carried out with the data. Educational outcomes were chosen as the dependent variable for measuring performance.Findings – The analysis indicates that financial resources are paramount in producing performance to the extent that resource availability increases educational effectiveness, and dependence on intergovernmental transfer of financial resources reduces the effectiveness a great deal. Some other issues, such as mayoral quality have little or no importance upon performance.Originality/value – The study corroborates some established ideas and challenges others. An example of the latter is the notion that the quality of political leadership (the mayor) is a determinant factor for performance. An example of the former is that more money is likely to represent better performance if the local government is able to raise money for itself instead of relying solely on transferences from upper tie authorities.